Дослідження шляхів інтенсифікації агломераційного процесу в умовах акціонерного товариства «Покровський гірничо-збагачувальний комбінат» - Шуваєв, Сергій; Семірягін, Сергій; Нізяєв, Костянтин; Бойко, Максим; Стоянов, Олександр; Ягольник, Максим (Physico-technological Institute of Metals and Alloys, 2023)
The use in the sinter charge of a large proportion of fine concentrate and waste metallurgical production, fluctuations in the composition of the sinter charge and the quality of its preparation, deviations from the norm of technological parameters of sintering and low efficiency of machined sintered product, reduces the productivity of sintering machines, leads to increased fuel consumption, degrades the quality of the sinter. Under such conditions, the importance of prepreparation of the charge and the necessary use of methods to intensify the sintering process increases. Currently, a significant number of ways to intensify the sintering process is known, the effectiveness of each depends on the specific conditions of the sinter plant, the installed equipment and raw materials used. The efficiency of various ways to increase the intensity of the sintering process and the quality of the sinter for the conditions of the Joint Stock Company “Pokrovskiy Girnycho-Zbagachuvalniy Kombinat” was investigated with the definition of rational technological measures aimed at improving the operation of the enterprise. The research was carried out on a laboratory sinter plant using charge materials and technological conditions of the Bogdanov sinter factory. According to the results of research, it is established that the size of charge materials used in the sinter plant exceeds the maximum allowable size. This reduces the technical and economic performance of the sintering process and prevents the production of high quality agglomerate. To improve the performance of sintering machines in the studied conditions, it is recommended to use pre-treatment of charge materials before use, namely crushing to obtain a rational particle size. In addition, the use of lime, as a partial replacement of limestone in the flux mixture, will improve the quality of the sinter.